1995
DOI: 10.1007/bf01457542
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cytokeratin expression in epidermal keratinocytes during wound healing

Abstract: In order to investigate the re-epithelialization process during wound healing, the hair on the back of guinea pigs was shaved and then excisional wounds were made through the entire thickness of the skin. Histological changes were observed and changes in the expression of different cytokeratin polypeptides were examined using an immunohistochemical technique. Immunohistochemical study revealed that the proliferating and migrating keratinocytes expressed the same cytokeratins as the basal cells of normal epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…These results further support a role for oxygen availability in keratinocyte differentiation, which is known specifically to be heavily dependent on energy synthesis [41,42]. Oxygen availability affects keratinocyte differentiation through mitochondrial reactive oxygen species mechanism [43] and improves differentiation to yield cytokeratin I and II expressing cells [44]. These results are supported by in vitro work that has shown that in low oxygen tensions (< 21%) keratinocyte differentiation is reduced as compared to responses in atmospheric oxygen [41].…”
Section: Discussionsupporting
confidence: 52%
“…These results further support a role for oxygen availability in keratinocyte differentiation, which is known specifically to be heavily dependent on energy synthesis [41,42]. Oxygen availability affects keratinocyte differentiation through mitochondrial reactive oxygen species mechanism [43] and improves differentiation to yield cytokeratin I and II expressing cells [44]. These results are supported by in vitro work that has shown that in low oxygen tensions (< 21%) keratinocyte differentiation is reduced as compared to responses in atmospheric oxygen [41].…”
Section: Discussionsupporting
confidence: 52%
“…The morphological changes in keratinocyte differentiation are furthermore associated with changes in the cytokeratins content [27]. In particular, CK1 is typically co-expressed with CK10 and both are differentiation specific keratins expressed in the suprabasal levels of epidermis [6].…”
Section: Discussionmentioning
confidence: 99%
“…In wound healing, the expression of the cytokeratins changes during phase of healing process, and position that keratinocytes have in healing tissue [11]. What this study revealed is that the migrating keratinocytes expressed same, basal cytokeratin.…”
Section: Discussionmentioning
confidence: 51%
“…Maturation of keratinocytes occurs simultaneously with their migration over the wound bed. Keratinocyte maturation is characterized with pool of cytokeratin, intermediate filament within the cell [11]. During the terminal differentiation of keratinocytes two major classes of proteins, namely tissue-specific cytokeratins on the one hand, and components of the cornified envelope (e.g.…”
Section: Introductionmentioning
confidence: 99%